Shanghai Express [videorecording (DVD)] - Dietrich, Marlene; Brook, Clive, 1887-1974; Wong, Anna May, 1905-1961; Oland, Warner, 1880-1938; Hervey, Harry, 1900-1951 (TCM vault collection., 2012)
Marlene Dietrich plays the notorious adventuress Shanghai Lily, who has been jilted by Captain Donald Harvey (Clive Brook). During the Chinese civil war, the couple meet on a train which is attacked by Chinese rebels. Dietrich becomes involved with a rebel leader in order to save the man she still loves.